Applying High Voltage Cathodic Pulse with Various Pulse Durations on Aluminium Via Micro-Arc Oxidation (MAO) - Yılmaz, Mustafa Safa; Şahin, Orhan (Elsevier, 2017)
The present study is an investigation of the effect of pulse duration on properties of coatings formed on aluminium alloy (Al) in alkaline solution via using of high voltage cathodic pulses. Nine different anodic-cathodic pulse couples with various durations were selected for processing. In order to find out the effect of pulse duration on coating: duty cycle, anodic voltage, cathodic voltage, processing time, electrolyte temperature and electrolyte composition were kept constant. Scanning electron microscope (SEM), profilometer, X-ray diffractometer and indenter were employed to investigate the microstructure, surface roughness, phase distribution and hardness of the coatings. Also, coating thickness measurement was carried out to find out the effect of pulse duration on productivity. Varying of pulse duration caused significant differences among thickness of coating layers. Coating layers with thickness between 45-75 μm and surface roughness between 2.5-5.5 μm were obtained. Coatings consist of two layers, outer porous layer and inner dense layer. The outer porous layer was γ-Al2O3 and the inner dense layer was a mixture of γ-Al2O3 and α-Al2O3. The hardness of inner dense layers was between 1100-1600 Vickers.
Keywords: Aluminium; Micro-Arc Oxidation; Pulse Duration; Coating